Devising a methodology to compare methods for selecting the optimal architectural variation of command query responsibility segregation with event sourcing - Hruzin, Dmytro; Lytvynov, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2026)
This study compares methods for evaluating software architecture. The work is aimed at improving the objectivity of such a comparison by using quantitative indicators obtained on the basis of a parametric model whose adequacy has been verified experimentally. This paper proposes a methodology to quantitatively compare methods for evaluating software architecture. This methodology enabled a comparison between the architectural trade-off analysis method (ATAM) and decision support technology for architectural variations in the Command Query Responsibility Segregation (CQRS) architecture with the event sourcing approach (DSAV-CQRSES). The methodology's feature is a parametric model built on the basis of an analysis of real projects, which makes it possible to substantiate the correctness of reference variation, as well as quantitative evaluation of the methods, in particular by the duration of application and the discrepancy of results. The proposed methodology has made it possible to quantitatively confirm the advantages of DSAV-CQRSES over ATAM for solving the task of choosing the optimal variation of CQRSES architecture. The duration of ATAM application was 32 hours with the participation of four specialists (total costs of 88 person-hours). The DSAV-CQRSES technology was used by one specialist for 40 hours. With the average and limit parameters of the model, DSAV-CQRSES robustly determined the recommended variation at a variance coefficient of 2.8%. In contrast, ATAM demonstrated lower accuracy and provided the correct choice in three out of five cases with a variation coefficient of 33.64%. The results of the experiment could be used in practice to select tools for comparing variations in the CQRSES architecture